A gramaticalização de verbos na Nova Gramática do Português Brasileiro - Ramacciotti, Adriana de Souza (2015)
The present work examines the grammaticalization of verbs in a Brazilian Portuguese grammar (Nova Gramática do Português Brasileiro), written by Ataliba Teixeira de Castilho. The primary purpose is to verify whether there is grammaticalization of verbs and the second one is to describe its pathway. Grammaticalization is a language change process which turns lexical items into grammatical forms and grammaticalized forms into more grammaticalized ones. It is an interesting subject to be used by Elementaty and High School Portuguese teachers. The research is mainly based on the following researchers: Castilho (1977), Givón (1979), Hopper (1991), Hopper & Traugott (2009), Lehmann (2002), Martelotta (2011) e Martelotta, Votre & Cezario (1996) e Heine (2003). The grammaticalized verbs were analysed according to Lehmann´s parameters (1985) and Hopper´s principles of grammaticalization (1991). Castilho´s grammar has traced that the ser, estar, ter, haver, ir, querer, poder and dever Brazilian Portuguese verbs has undergone grammaticalization from full to auxiliary verbs. Grammaticalization process is also related to the foi fez construction